Tuning pathological brain oscillations with neurofeedback: a systems neuroscience framework - Ros, Tomas; J. Baars, Bernard; Lanius, Ruth A.; Vuilleumier, Patrik (Frontiers in Human Neuroscience, 2014)
Neurofeedback is emerging as a promising technique that enables self-regulation of ongoing brain oscillations. However, despite a rise in empirical evidence attesting to its clinical benefits, a solid theoretical basis is still lacking on the manner in which neurofeedback is able to achieve these outcomes. The present work attempts to bring together various concepts from neurobiology, engineering, and dynamical systems so as to propose a contemporary theoretical framework for the mechanistic effects of neurofeedback. The objective is to provide a firmly neurophysiological account of neurofeedback, which goes beyond traditional behaviorist interpretations that attempt to explain psychological processes solely from a descriptive standpoint whilst treating the brain as a ‘black box’. To this end, we interlink evidence from experimental findings that encompass a broad range of intrinsic brain phenomena: starting from ‘bottom-up’ mechanisms of neural synchronization, followed by ‘top-down’ regulation of internal brain states, moving to dynamical systems plus control-theoretic principles, and concluding with activity-dependent as well as homeostatic forms of brain plasticity. In support of our framework, we examine the effects of neurofeedback in several brain disorders, including attention-deficit hyperactivity (ADHD) and post-traumatic stress disorder (PTSD). The central thesis put forward is that neurofeedback tunes brain oscillations toward a homeostatic set-point which maintains optimal network flexibility and stability (i.e. self-organized criticality).